Market Processes and Thwarting Systems - Piero Ferri; Hyman P. Minsky (Levy Economics Institute of Bard College, 1991)
This paper suggests that there are two longstanding views on business cycles and economic dynamics: One emphasizes endogenous stability plus exogenous disturbances, while the other focuses on endogenous instability plus institutional 'containing' or "thwarting" mechanisms. The latter tradition regards business cycles and economic instability as the natural and inherent consequence of self-interest-motivated behavior in complex economies with sophisticated financial institutions. In fact, it is the interaction between the system's endoge-nous dynamics and the effects of institutions and interventions which, if "apt," constrains the outcomes of capitalist market processes to acceptable outcomes. The endogenous instability view of the economy, in which institutional structures and interventions stabilize the fragile, essentially refutes Lucas: He asserts that the economy is a mechanism that transforms exogenous shocks (either random or unanticipated policy interventions) into business cycles, thus generating a growth equilibrium. Recent history has illustrated the flaws of laissez-faire theory as the postwar capitalist economies that have enjoyed consistently high levels of growth are big government interventionist economies. The challenge for the future is recognizing that market processes are deficient not only in their ability to maintain aggregate demand, but also as devices for assuring productive investment and a tolerable distribution of income.
Keywords: 330